(untitled) (Web of Teachers: Inderscience Research, 2024)
Multimedia technologies have revolutionized English language teaching, offering dynamic and interactive tools that enhance the learning experience. By incorporating audio, video, animations, and interactive platforms, educators can address diverse learning styles, foster engagement, and create authentic language contexts. The use of multimedia tools such as language learning apps, online platforms, video conferencing tools, and gamified learning environments has demonstrated significant improvements in student outcomes, particularly in listening, speaking, reading, and writing skills. This article explores the role of multimedia in English language teaching, examines its impact on pedagogy, and provides insights into the challenges and opportunities presented by multimedia technologies in the classroom. Finally, it discusses strategies for effective integration and the importance of teacher training in optimizing multimedia use for language acquisition.